(3NjGdjGJs - (3eSYhO, QGfjGs; (3jSWQhfs ((3LjRI, eUQs (3cJGH Wjhas, 2017)
(3GdNjGdI(B.. (3gi GdJQLeI GdebJQMI dcdeI (B"(3GdSjfeG(B" (3haj gPG GdcJGH fMf CeGe eTGgO EfSGfjI HGdZI GdQgGaI, JJYdb HgPG Gdaf GdeOgT, heG bOeg dfG ef CadGe hTNUjGJ, YTfG eYgG hScHfG YdjgG ef eTGYQfG hCacGQfG, HMjK fSJWjY Cf fbhd EfgG MaQJ HUeGJgG Ydi GdYbd hGdhLOGf hGdPGcQI, GdeDdaI NdbJ YhGdegG GdNGUI GdJj JSddJ EdjgG eTGgO GdNjGdI HMjK jeJRL aj gPI GdYhGde eG gh Mbjbj HeG gh NjGdj, HeG gh NGQL ef CacGQ GdeDdaI heTGYQgG(B. (3hdCf GdeDdaI Jedc KbGaI eJYOOI GdefGMj, aEfgG JeRL gPg GdQDi HeYWjGJ gPg GdKbGaI GdQMHI, dJbOe dfG dhMGJ EfSGfjI eOgTI aj cJGH eeJY, gh djS cJGHkG aj GdfbO GdCOHj HbOQ eG gh dhMGJ COHjI PGJ WGHY EfSGfj TOjO GdNUhUjI, jNdb MhGQkG NGUkG eY YOO ef GdCadGe hGdTNUjGJ hGdeTGYQ dfcJTa Cfg aj GdMbjbI EfeG jbje MhGQkG NGUkG eYfG fMf, heY PcQjGJfG hQDGfG heTGYQfGs
(3cJGH Wjha SdSdI ef CUOQGJ jSWQhfs
1 13
Keywords: (3GdCadGe GdSjfeGFjIs -- (3JGQjN hfbOs; (3GdSjfeGs -- (3fbOs; (3GdebGdGJs